Effect of Biomarkers on Predicting Mortality in COVID-19 Pneumonias: A Retrospective Clinical Study - Tamer Durdu; Habibe Selmin Özensoy; Hakan Oğuztürk (Global Emergency and Critical Care)
Objective: Coronavirus disease-2019 (COVID-19) remains a significant challenge in emergency services worldwide. This study investigated the relationship between hematocrit (Htc), hemoglobin (Hb), amylase, lactate, and interleukin 6 (IL-6) levels and hospitalization and mortality in patients diagnosed with COVID-19. Materials and Methods: Htc, Hb, amylase, lipase, lactate, and Interleukin 6 (IL-6) levels of patients with a positive COVID-19 polymerase chain reaction (PCR) test (Bio-speedy® Severe acute respiratory syndrome-Coronavirus-2 Triple Gene Reverse transcription quantitative PCR, Türkiye) who presented to the emergency department were analyzed. Hospitalizations and short-term (28 days) mortality were retrospectively examined. The data were analyzed using SPSS for Windows 20.0. Normality analysis of continuous data was conducted using the Shapiro-Wilk test. Multiple logistic regression analysis was performed to analyze predictors of mortality and discharge. Results: Data from 6,627 emergency department patients were examined. The gender (p<0.001), age (p<0.001), Hb (p<0.001), lactate (p<0.001), and lipase (p<0.001) levels of the hospitalized patients. Increasing age was associated with mortality (p<0.001). In the analysis of biomarkers, a decrease in Hb and Htc (p<0.001; p=0.038) and an increase in lactate, lipase, amylase, and IL-6 (p<0.001; p<0.001; p=0.022; p<0.001) were determined to be associated with mortality. The area under the receiver operating characteristic curve for the mortality model was calculated as 0.724, with specificity and sensitivity determined as 91.8% and 97.5%, respectively. Conclusion: Age, amylase, lipase, serum lactate, and interleukin-6 levels, when calculated together, are important predictors of both mortality and hospitalization in COVID-19 pneumonia.